The Implementation of a Large-Scale Pathway Reform: How Department Chairs Make Sense of and Navigate a Pathway Initiative in a Community College. Issue 9 (2nd September 2021) - Chase, Megan Michaelene; Bensimon, Estela; Robinson, Jason
ABSTRACT: Nationally, the pathway model – commonly defined as "a highly structured, coherent education experience that is built around and through an area of study" – has emerged as the preferred structural approach to deliver the curriculum at community colleges. The pathway model provides a new hope to community colleges to create a solution to low completion rates. However, the current literature on successful implementation is almost non-existent, therefore, without such directions on how to assemble the pathway model, college practitioners, specifically department chairs, are left to interpret and act on the pathway reform in a variety of ways. The purpose of this paper is to describe how department chairs understand the pathway model and how they subsequently implement it in their programs. Utilizing a case study design, we document how department chairs made sense of the reform and the processes of implementation. We found that department chairs' explanations of the pathway reform fell into three types, influencing how they acted on the reform. This study highlights the complexity of implementing large-scale institutional change and the important role department chairs play in the successful implementation of a pathways reform.